Gastrointestinal stromal tumor of the stomach with lymph node metastasis treated by laparoscopic and endoscopic cooperative surgery with lymph node pick-up resection: A case report and literature review. (2020) - Kubota, Akira; Kuwabara, Shirou; Yamaguchi, Kenzi; Kobayashi, Kazuaki; Hashidate, Hideki
Highlights: We performed LECS with pick-up lymph node dissection for GIST of the stomach with lymph node metastasis. LECS with pick-up lymph node dissection allows minimal gastric resection for GIST of the stomach with lymph node metastasis. The endoscopy was useful for giving us exact resection margins using this magnification view. Abstract: Introduction: Gastrointestinal stromal tumor of the stomach with lymph node metastasis is a rare condition, and few cases have been treated by gastrectomy and systematic lymph node dissection. Presentation of case: We report the case of a patient who was treated by local resection with laparoscopic and endoscopic cooperative surgery and lymph node pick-up resection. A 73-year-old woman presented with gastric submucosal tumor and swollen lymph node. The submucosal tumor was 30 mm in size. After surgery, the tumor was confirmed to be a gastrointestinal stromal tumor by immunostaining. No recurrence was noted 36 months following the surgery. Discussion: Laparoscopic and endoscopic cooperative surgery allows minimal resection because the exact resection margin can be identified. Therefore, endoscopy is a useful aid in the treatment of gastric gastrointestinal stromal tumor. The MIB-1 index of metastatic lymph node was lower than that of a primary lesion; hence, the prognosis might not depend on lymph node metastasis. Conclusion: Laparoscopic and endoscopic cooperative surgery and lymph node pick-up resection were useful and minimally invasive. Systematic lymph node dissection is not a viable option.